PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN IV SEBAGAI UPAYA PENINGKATAN PEMBELAJARAN PESERTA DIDIK DI SD NEGERI 69 ITTERUNG BONE - Nurjaya (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2024)
The Independent Campus Teaching and Learning Campus Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. One of the schools targeted by the Teaching Campus program is SD Negeri 69 Itterung which is located in Tokebo Hamlet, Itterung Village, Tellu Siattingnge District, Bone Regency. The Teaching Campus Program is implemented in the form of assisting the teaching and learning process, assisting with technology adaptation, and assisting school administration